Glutamine metabolism in breast cancer and possible therapeutic targets - Li, Shiqi; Zeng, Hui; Fan, Junli; Wang, Fubing; Xu, Chen; Li, Yirong; Tu, Jiancheng; Nephew, Kenneth P.; Long, Xinghua (Biochemical pharmacology, 2023)
[Display omitted] Cancer is characterized by metabolic reprogramming, which is a hot topic in tumor treatment research. Cancer cells alter metabolic pathways to promote their growth, and the common purpose of these altered metabolic pathways is to adapt the metabolic state to the uncontrolled proliferation of cancer cells. Most cancer cells in a state of nonhypoxia will increase the uptake of glucose and produce lactate, called the Warburg effect. Increased glucose consumption is used as a carbon source to support cell proliferation, including nucleotide, lipid and protein synthesis. In the Warburg effect, pyruvate dehydrogenase activity decreases, thereby disrupting the TCA cycle. In addition to glucose, glutamine is also an important nutrient for the growth and proliferation of cancer cells, an important carbon bank and nitrogen bank for the growth and proliferation of cancer cells, providing ribose, nonessential amino acids, citrate, and glycerin necessary for cancer cell growth and proliferation and compensating for the reduction in oxidative phosphorylation pathways in cancer cells caused by the Warburg effect. In human plasma, glutamine is the most abundant amino acid. Normal cells produce glutamine via glutamine synthase (GLS), but the glutamine synthesized by tumor cells is insufficient to meet their high growth needs, resulting in a “glutamine-dependent phenomenon.” Most cancers have an increased glutamine demand, including breast cancer. Metabolic reprogramming not only enables tumor cells to maintain the reduction–oxidation (redox) balance and commit resources to biosynthesis but also establishes heterogeneous metabolic phenotypes of tumor cells that are distinct from those of nontumor cells. Thus, targeting the metabolic differences between tumor and nontumor cells may be a promising and novel anticancer strategy. Glutamine metabolic compartments have emerged as promising candidates, especially in TNBC and drug-resistant breast cancer. In this review, the latest discoveries of breast cancer and glutamine metabolism are discussed, novel treatment methods based on amino acid transporters and glutaminase are discussed, and the relationship between glutamine metabolism and breast cancer metastasis, drug resistance, tumor immunity and ferroptosis are explained, which provides new ideas for the clinical treatment of breast cancer.